-2.3-3x-4.1-x=-3x-0.9

Simple and best practice solution for -2.3-3x-4.1-x=-3x-0.9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2.3-3x-4.1-x=-3x-0.9 equation:


Simplifying
-2.3 + -3x + -4.1 + -1x = -3x + -0.9

Reorder the terms:
-2.3 + -4.1 + -3x + -1x = -3x + -0.9

Combine like terms: -2.3 + -4.1 = -6.4
-6.4 + -3x + -1x = -3x + -0.9

Combine like terms: -3x + -1x = -4x
-6.4 + -4x = -3x + -0.9

Reorder the terms:
-6.4 + -4x = -0.9 + -3x

Solving
-6.4 + -4x = -0.9 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-6.4 + -4x + 3x = -0.9 + -3x + 3x

Combine like terms: -4x + 3x = -1x
-6.4 + -1x = -0.9 + -3x + 3x

Combine like terms: -3x + 3x = 0
-6.4 + -1x = -0.9 + 0
-6.4 + -1x = -0.9

Add '6.4' to each side of the equation.
-6.4 + 6.4 + -1x = -0.9 + 6.4

Combine like terms: -6.4 + 6.4 = 0.0
0.0 + -1x = -0.9 + 6.4
-1x = -0.9 + 6.4

Combine like terms: -0.9 + 6.4 = 5.5
-1x = 5.5

Divide each side by '-1'.
x = -5.5

Simplifying
x = -5.5

See similar equations:

| ln(3x-6)=8 | | K+12=10 | | K+10=10 | | 3x-2x+8=5x+5+3 | | -2+n=6n+22 | | -3=-15-3x | | 5a-3=a+45 | | M+22=50 | | K+18=36 | | W+39=39 | | K+21=42 | | N+36=36 | | 10x-8+136=180 | | (2d+4)=35 | | K+24=36 | | -6x+21-10=9-10x-8 | | 2x-16+x=2x-12+2 | | X+33=50 | | M+32=40 | | 7x/14x | | M+12=12 | | 1.75x+1.50y=337.50 | | 4/3x=90 | | 29(v-990)=-232 | | x^4=0.207 | | 5x=(250/4) | | 16x-3+9x+11+52=180 | | 870=10(w+40) | | C+20=10 | | 16x-3+9x+11=52 | | 111-3s=63 | | 15(z+406)=240 |

Equations solver categories